Assessing Pedagogical Innovations: Empowering Excellence with OSVE in Undergraduate MBBS Students at Rai Medical College,Sargodha - Mudaser hussain Abbasi; Kamran Arzoo; Muhammad Hammad Jatalla; Sundas Ahmad; Tanveer ZIa Qureshi; Zahid Masood (Journal of Aziz Fatimah Medical and Dental College)
Objectives: To explores the perception & effectiveness of objectively structured viva examinations (OSVE) in 3rd year MBBS students as compared to routine general viva for future implementation at Rai Medical College, Sargodha.